Effect of tightening zone length of reinforced concrete beams on beam capacity - Sinan Cansız (Građevinar)
This study investigated seismic analysis of the behavior of reinforced concrete beams with various shear spans, stirrup shapes, and tightening zone lengths using the Seismo-struct 2020 program. The load–displacement relations of 24 reinforced concrete beams with different conditions were modeled analytically. The analytical model used in the study was validated by comparing it with the experimental data from the literature. It was found that increasing the length of the tightening zone, particularly in beams with a high shear span, is essential for earthquake safety. In addition, the backbone curve of each beam was extracted, and comparison graphs were analyzed. The results obtained demonstrated that the length of the tightening zone limits the effect of stirrup shape and diameter on beam behavior.